Internalization of Social Care Character among Female Santri through the Safari Dakwah Program - Siti Chomsiatin Binti Ni’matul Ummah; Happy Susanto; Miftah Hur Rahman Zh (International Journal of Learning and Education, 2025)
This study aims to comprehend and describe the internalization of social care character among female students through the dakwah safari program. Conducted at Pondok Pesantren Ainul Mardhiyyah in Jetis District, Ponorogo Regency, East Java, Indonesia. This research employs a descriptive qualitative approach. Data collection methods include interviews, observations, and documentation, with data analyzed using descriptive analysis. Findings indicate that the promotion of social care character by the Ministry of Education and Culture and the Ministry of Religious Affairs synergizes well for students in Indonesia. The internalization of social care character among female students at Pesantren Ainul Mardhiyyah has been effectively implemented through the dakwah safari program. This program has demonstrated its effectiveness in enhancing students' social care character, particularly in honesty, discipline, responsibility, politeness, self-confidence, and compassion for others. Furthermore, the internalization process involves several steps, including providing practical knowledge such as Islamic jurisprudence, etiquette, culture, public speaking, and Quran recitation to female students, strengthening their faith, and refining their vision and mission of the pesantren. These activities have positively impacted female students, preparing them effectively for real-life challenges in society.